Low-cost fabrication of flexible transparent electrodes based on Al doped ZnO and silver nanowire nanocomposites: impact of the network density. Issue 25 (11th June 2019) - Nguyen, Viet Huong; Resende, Joao; Papanastasiou, Dorina T.; Fontanals, Nil; Jiménez, Carmen; Muñoz-Rojas, David; Bellet, Daniel
Abstract : Nanocomposites based on AgNWs and Al doped ZnO yields transparent electrodes with superior performances. Abstract : We report the study of nanocomposite transparent electrodes based on aluminium doped zinc oxide (ZnO : Al) thin films and silver nanowire (AgNW) networks. The electrodes are fully fabricated by low-cost, open-air techniques, namely, atmospheric pressure spatial atomic layer deposition and spray coating. We show that the transparency and the electrical conductivity of the ZnO : Al/AgNW nanocomposites can be tuned by controlling the AgNW network density. We also demonstrate that the thermal, electrical and mechanical stabilities of the nanocomposites are drastically enhanced compared to those of AgNW networks or ZnO : Al thin films separately. Interestingly, we report a clear continuous decrease of the electrical resistance of the nanocomposites for network densities even below the percolation threshold. We propose a model to explain the relationship between the conductivity of the nanocomposites and the AgNW network density. Our physical model is based on the non-negligible contribution of percolating clusters of AgNWs for network densities below the percolation threshold. Our results provide a means to predicting the physical properties of such nanocomposites for applications in solar cells and other optoelectronic devices. Finally, the deposition methods used open the way towards stable, low-cost and flexible transparent electrodes for industrial applications.